Causal Loop Diagram of Microtakaful Framework Model with the Integration of Zakat and Waqf - Idham Mohamad, Arwin; Zainal Abidin, Norhaslinda; Zulkepli, Jafri (International Journal of Engineering and Technology, 2019)
One of the mechanism to provide financial assistant and reduce poverty of the poor is microinsurance or microtakaful. As Islamic institutions, Zakat and Waqf can play an important role providing this microtakaful benefit to the poor as well as reducing the risk of uncertainty in contribution. Even though there are differences in concepts and structure in zakat and waqf, the integration of both institutions will help local zakat authorities and waqf institutions to provide microtakaful benefits as a financial protection to the poor. The aim of this paper is to develop a causal loop diagram (CLD) of the integration of zakat and waqf in providing microtakaful benefit. CLD is one of the important tool in system dynamics approach that helps in visualizing the major variables and the cause and effect relationship between zakat and waqf in a holistic microtakaful model. CLD can be used as a support to the framework in order to ensure the continuity and sustainability of the microtakaful model. This approach will help in visualizing the integration of changes between both zakat and waqf components and the impact of those changes through positive (+) and negative (-) symbol, and balancing and reinforcing of relationships that may result in insolvency of the microtakaful system. The proposed framework model can be used in the long term without having to penalize the parties involved, either the operator, or the participants in order to provide financial protection to the poor. The framework can be useful to the local Zakat authorities and Islamic council on the idea of mutual assistance funds planning to help in uplifting the life of poor and this is one of the urgent agenda for our country.Â Â
Keywords: microtakaful; integration zakat and waqf; causal loop diagram; system dynamics.